1999
DOI: 10.1177/154193129904300902
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of Responsibility for Injuries from a “Hidden” Hazard

Abstract: Safety researchers have investigated how people assign blame for injuries sustained during the use of or exposure to consumer products. In this study, we examine attributions made by people given product-use scenarios that describe a girl whose age is manipulated to be from 18 months to 16 years and who suffers serious brain damage after choking on marshmallows made available to her by her mother. Supplementary information intended to be either positive or detrimental to the manufacturer and its safety practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Confirming our expectation, and consistent with past research (Kalsher et al, 1999), participants perceived low risk associated with eating marshmallows. The mean hazard rating was 1.44 (on a scale from 0 =no risk to 6 =high risk) and 75% of participants indicated that they would give marshmallows to their children to eat (65% indicated they would give them to someone else's children to eat).…”
Section: Risk Perceptionssupporting
confidence: 94%
See 3 more Smart Citations
“…Confirming our expectation, and consistent with past research (Kalsher et al, 1999), participants perceived low risk associated with eating marshmallows. The mean hazard rating was 1.44 (on a scale from 0 =no risk to 6 =high risk) and 75% of participants indicated that they would give marshmallows to their children to eat (65% indicated they would give them to someone else's children to eat).…”
Section: Risk Perceptionssupporting
confidence: 94%
“…Providing positive information about the manufacturer (including a warning) increased the blame placed on parents relative to others. Kalsher et al (1999) also found that blame allocations varied with the victim's age. Responsibility assigned to the victim was a positive linear function of the victim's age, whereas responsibility…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The objective of the current set of experiments was to establish a pictorial warning for the choking hazard associated with marshmallows. Previous research by Kalsher, Wogalter, and Williams (1999) indicated that people do not perceive eating marshmallows to be hazardous, despite the fact that many children either die through suffocation, or are permanently injured after choking on them, or related types offood. In Experiment 1, participants used the comprehension estimation procedure to determine the probability that each of 15 pictorial symbols would accurately depict the choking hazard.…”
Section: Introductionmentioning
confidence: 99%